Six-month humoral and cellular immune response to the third dose of BNT162b2 anti-SARS-CoV-2 vaccine in patients with solid tumors: a longitudinal cohort study with a focus on the variants of concern - Lasagna, A.; Bergami, F.; Lilleri, D.; Percivalle, E.; Quaccini, M.; Serra, F.; Comolli, G.; Sarasini, A.; Sammartino, J.C.; Ferrari, A.; Arena, F.; Secondino, S.; et al. (ESMO open, 2022)
The role and the durability of the immunogenicity of the third dose of vaccine against COVID-19 variants of concern in cancer patients have to be elucidated. We have prospectively evaluated the immunogenicity of the third dose of the SARS-CoV-2 BNT162b2 messenger RNA vaccine in triggering both humoral and cell-mediated immune response in patients with solid tumors undergoing active treatment 6 months after the booster. Neutralizing antibody (NT Ab) titers and total anti-spike immunoglobulin G concentrations were measured in serum. Heparinized whole blood samples were used for the SARS-CoV-2 interferon-γ release assay (IGRA). Six months after the third dose only two patients (2.4%) showed negative spike-specific immunoglobulin G antibody levels (<33.8 BAU/ml). The median level of SARS-CoV-2 NT Abs decreased and only 39/83 (47%) subjects showed maximum levels of NT Abs. T-cellular positive response was observed in 38/61 (62.3%) patients; the highest median level of response was observed 21 days after the third dose (354 mIU/ml, interquartile range 83.3-846.3 mIU/ml). The lowest median level of NT Ab response was observed against the Omicron variant (1 : 10, interquartile range 1 : 10-1 : 40) with a significant reduced rate of responder subjects with respect to the wild-type strain (77.5% versus 95%; P = 0.0022) and Delta variant (77.5% versus 93.7%; P = 0.0053). During the follow-up period, seven patients (8%) had a confirmed post-vaccination infection, but none of them required hospitalization or oxygen therapy. Our work highlights a significant humoral and cellular immune response among patients with solid tumors 6 months after the third BNT162b2 vaccine dose, although a reduction in neutralizing activity against Omicron was observed. •Only two patients (2.4%) showed negative spike-specific IgG antibody levels (<33.8 BAU/ml)•Only 39/83 (47%) subjects showed maximum level of neutralizing antibodies (NT Abs).•T-cellular positive response was observed in 38/61 (62.3%) analyzed patients.•The lowest median level of NT Ab response was observed against the Omicron variant.•Seven patients (8%) had a post-vaccination infection; none of them required hospitalization or oxygen therapy.